1999
DOI: 10.1128/iai.67.7.3667-3669.1999
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a sigB Deletion Mutant of Staphylococcus aureus

Abstract: The sigB gene of Staphylococcus aureus, coding for the alternate sigma factor B, has been deleted by allelic replacement mutagenesis. The mutant grew as well as the parent in vitro, although it was deficient in clumping factor, coagulase, and pigment. In two murine and one rat infection model the mutant showed no reduction in virulence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…Upregulation of sigB was described as downregulating protease production but additionally promoting expression of adherence factors that aid in initial biofilm formation (4,23). Staphylococcal capsules are important in the pathogenesis of S. aureus infections.…”
Section: Resultsmentioning
confidence: 99%
“…Upregulation of sigB was described as downregulating protease production but additionally promoting expression of adherence factors that aid in initial biofilm formation (4,23). Staphylococcal capsules are important in the pathogenesis of S. aureus infections.…”
Section: Resultsmentioning
confidence: 99%
“…As the promoter region between Newman and RN6390 is identical, the downregulation of hla in strain Newman can probably be explained by differences in trans ‐acting mechanisms. Recently, it was shown that SarA upregulates the alternative σ‐factor, sig B (Chan et al ., 1998), which in turn inhibits hla transcription (Cheung et al ., 1999; Nicholas et al ., 1999;Giachino et al ., 2001). Strain Newman contains an intact sig B operon, which probably accounts for the downregulation of hla in vitro (Giachino et al ., 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, deletion of the second hla repressor, sar H1, did not result in enhanced hla transcription in an agr ‐negative background (Tegmark et al ., 2000). Furthermore, it has been shown that mutation in sig B (Cheung et al ., 1999; Nicholas et al ., 1999) and in the activator of sig B, rsb U (Giachino et al ., 2001), leads to increased hla transcription.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to sarA and agr, sigB has not been found to play major roles in acute models of infections (106).…”
Section: The Role Of Global Regulators In Virulencementioning
confidence: 97%